PROBLEMATIKA VISA IZIN TINGGAL KUNJUNGAN LEWAT BATAS WAKTU (OVERSTAY) PADA WARGA NEGARA ASING (WNA): SUATU TINJAUAN KEBIJAKAN HUKUM PIDANA - Jhonsen Marudut; Indra Yudha Koswara (Jurnal Hukum Mimbar Justitia, 2023)
Criminal law policy according to Criminal law policy regarding crime and punishment is an important part of criminal law reform, and is even seen as an indicator of the progress of a nation. The current Criminal Code, a legacy of the Netherlands, is still heavily influenced by the classical school and places imprisonment as the prima donna. The result is a high rate of imprisonment, as well as an impact on excess capacity in correctional institutions, as well as problems with funding and training for prisoners. Stay permits are issued or issued by the Immigration Office, which is an institution that regulates issues regarding the movement of foreigners into the territory of the Republic of Indonesia which is implemented based on selective policy. This research aims to examine how criminal law policies can resolve criminal acts regarding misuse of visas for visiting stay permits beyond the deadline (overstay) among foreign nationals and how the immigration authorities enforce the law against these criminal acts. The research results show that the Criminal Law Policy aims to protect the community to achieve community welfare, so in terms of legal response to overstaying, this is translated into the principle of subsidiarity in criminal law, namely prioritizing the principle of ultimum remedium in lawcriminal, then administrative resolution is a more appropriate policy and regarding targets and action against Overstay must be in accordance with Law Number 6 of 2011 concerning Immigration and Presidential Regulation Number 21 of 2016 concerning Free Visitor Visas, by means of supervisioncompleteness of administrative procedures for residence permits for visits by foreigners, and taking administrative action against those who violate residence permits by charging foreigners to pay fees and repatriation to their country of origin Keywords: Criminal Policy; Expired Time Limit; Ultimum Remedium.